Construction of live vaccines using genetically engineered poxviruses: biological activity of vaccinia virus recombinants expressing the hepatitis B virus surface antigen and the herpes simplex virus glycoprotein D. - Paoletti, E (1984)
Potential live vaccines using recombinant vaccinia viruses have been constructed for both hepatitis B and herpes simplex. These recombinant vaccinia viruses express cloned genes of the hepatitis B virus surface antigen (HBsAg) or the glycoprotein D from herpes simplex virus (HSV-gD). The HBsAg synthesized in vitro under the regulation of vaccinia virus is secreted from infected cells as a particle of approximately equal to 22 nm diameter with a density of 1.2 g/ml as determined on CsCl gradients. Inoculation of rabbits with the recombinant vaccinia virus that expresses the HBsAg elicits the production of high-titered antibodies. Synthesis of the HSV-gD was detected in tissue culture by radioimmunoassay on unfixed cells, suggesting that the HSV-gD synthesized by the recombinant vaccinia virus is membrane associated. Inoculation of rabbits with the recombinant vaccinia virus expressing HSV-gD resulted in the production of antibodies that reacted with authentic HSV-gD as detected by radioimmunoassay. Furthermore, the anti-serum was shown by plaque-reduction assay to neutralize the infectivity of herpes simplex virus. Immunization of mice with the vaccinia recombinant expressing HSV-gD gave complete protection on subsequent challenge with lethal doses of live herpes simplex virus.